Modification of Cognitive Processes through Structural Conflicts with Formal Gamification Applications - Diaz-Riva, Meliza (2021)
Gamification from the use of platforms in virtual environments, has served for various studies with findings in structural learning. However, there is little evidence in the use of formal gamification platforms that include cognitive conflict from its pedagogical utility. The research has been carried out applying an experimental design with pretest and posttest measurements. We apply two types of cognitive conflict which we call Gamification Packages / Cognitive Packages. We used formal gamifiers (Mural.ly, Mentimeter, Google Jamboard, Kahoot!), applied in three experimental comparison groups of 150 students (M = 13,2 years; SD = 2,03). Reading, math, reasoning, and research science assignments were assessed. The findings reported greater effects in the group that received the Gamification Packages, secondly, the effects of Cognitive Packages,